Resolution of Pseudoainhum with Acitretin in Lamellar Ichthyosis - Sukumar, Srisukhirthi; Pavadai, Nithiyaa; Kuruvila, Sheela (Nepal Journal of Dermatology, Venereology & Leprology, 2025)
Lamellar ichthyosis is an autosomal recessive type of ichthyosis characterized by abnormal skin scaling, ectropion and ear abnormalities. Pseudoainhum is the appearance of constriction bands around digits which can lead to autoamputation of digits. Here we report a case of Lamellar ichthyosis with Pseudoainhum, which showed reversal of Pseudoainhum with 6 months of acitretin therapy.